2001
DOI: 10.4269/ajtmh.2001.64.223
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine/doxycycline combination versus chloroquine alone, and doxycycline alone for the treatment of Plasmodium falciparum and Plasmodium vivax malaria in northeastern Irian Jaya, Indonesia.

Abstract: Abstract. Combination therapy is one method of overcoming the global challenge of drug-resistant Plasmodium falciparum malaria. We conducted a hospital-based 28-day in vivo test comparing chloroquine/doxycycline to chloroquine or doxycycline alone for treating P. falciparum and Plasmodium vivax malaria in Irian Jaya, Indonesia. Eighty-nine patients with uncomplicated falciparum malaria were randomized to standard dose chloroquine (n ϭ 30), doxycycline (100 mg every 12 hours [7 days], n ϭ 20), or chloroquine wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 33 publications
0
39
1
Order By: Relevance
“…Among 88 subjects treated up to 1995, 41% had a response consistent with resistance (8,81). Among 282 subjects evaluated since then, 39% were infected with resistant isolates (9,11,48,52,102,106). However, all 38 subjects evaluated on a small, isolated island in Papua had infections with sensitive organisms (52).…”
Section: Geographic Range Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Among 88 subjects treated up to 1995, 41% had a response consistent with resistance (8,81). Among 282 subjects evaluated since then, 39% were infected with resistant isolates (9,11,48,52,102,106). However, all 38 subjects evaluated on a small, isolated island in Papua had infections with sensitive organisms (52).…”
Section: Geographic Range Of Resistancementioning
confidence: 99%
“…Ohrt et al (85) demonstrated the complete efficacy of mefloquine for prophylaxis against the CRPV strain known to occur in northeastern Indonesian New Guinea. However, they also found that daily doxycycline had complete efficacy against CRPV, and Taylor et al (106) showed doxycycline monotherapy to have only 33% efficacy against CRPV. Clinical trials of mefloquine against CRPV are needed.…”
Section: Alternative Therapiesmentioning
confidence: 99%
“…Effective therapies for chloroquine-resistant P. vivax A few reports describe the efficacy of approved drugs for the treatment of P. vivax [50][51][52][53], and some reports describe treatments for CQ-resistant P. vivax [54][55][56]. Mefloquine (MQ) combined with PQ was effective in Papua, Indonesia (98% efficacy) [47], and CQ combined with PQ was much more effective than CQ alone [47,54].…”
Section: Failing Chloroquine Therapymentioning
confidence: 99%
“…These findings also corroborate the very high risk of therapeutic failure with chloroquine monotherapy against P. falciparum acquired in northeastern Papua, Indonesia. [7][8][9] …”
Section: Introductionmentioning
confidence: 99%